Inflammatory complications of vocal fold injection with hyaluronic acid: a multiinstitutional study - ENVER, NECATİ (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2021)
Background/aim: This study aimed to assess the inflammatory adverse reactions of vocal fold injection laryngoplasty with hyaluronic acid. Materials and methods: This study was a retrospective chart review of patients who underwent vocal fold injection augmentation with HA injection from January 2005 to September 2016 in nine different institutions. Demographic data, indication for injection, injection techniques, types of injection material, settings of procedure, and complications were reviewed. The types of complication, onset time, and management of complications were also noted. Results: In all, 467 patients were identified. The majority of patients had been injected under general anesthesia (n = 382, 84.7%). For injection material, two different types of hyaluronic acid were used: hyaluronic acid alone or hyaluronic acid with dextranomer. Complications occurred in nine patients (1.9%). The majority of complications were inflammatory reactions (n = 7, 1.47%). Main symptoms were dysphonia and/or dyspnea with an onset of 0 h to 3 weeks after the hyaluronic acid injection. Three patients were hospitalized, one of which was also intubated and observed in the intensive care unit for 24 h. Systemic steroids and antibiotics were the main medical treatment in the majority of cases. There was no statistical difference in complication rates between patients who received hyaluronic acid and those who received hyaluronic acid with dextranomer (P = 0.220). Conclusion: Hyaluronic acid can be considered as a safe substance for the injection of vocal folds with a low risk of inflammatory reaction.
Keywords: Vocal fold injection; hyaluronic acid; hyaluronic acid with dextranomer; inflammatory reaction; vocal fold paralysis; sulcus vocalis; INJECTABLE FILLERS; LARYNGOPLASTY